Analisis Pengaruh Narrative Involment Pada Impulsive Buying Yang Dimediasi Parasocial Interaction Dan Social Attractivness Terhadap Food Vlogger @Gemarkulineran - Kuswati, Rini; Rizky?, Vatri Aulia (YUME : Journal of Management, 2024)
This research endeavors to examine how Narrative Involvement impacts Impulsive Buying, with Parasocial Interaction and Social Attractiveness as mediating factors, focusing specifically on the influence of Food Vlogger @gemarkulineran. The research utilizes a quantitative methodology, employing purposive sampling instead of probability sampling. The primary data collection method involves distributing a structured questionnaire via Google Form, utilizing a Likert scale to gather responses. The research encompasses 157 respondents following @gemarkulineran. The analysis employs PLS-SEM, a method suitable for predicting and exploring complex models under less stringent data conditions. PLS-SEM is deemed appropriate due to its flexibility in accommodating such complexities. Subsequently, the collected data is analyzed using PLS with the assistance of SMARTPLS. The finding of this investigation reveal. Social attractiveness and Parasocial Interaction mediate the relationship between Narrative Involvement and Impulsive buying.Keywords : Narrative Involment, Parasocial Interaction, Social Attractivness, Impulsive Buying